The anterolateral ligament is a secondary stabilizer in the knee joint: A validated computational model of the biomechanical effects of a deficient anterior cruciate ligament and anterolateral ligament on knee joint kinematics. Issue 11 (November 2019) - Kang, Kyoung-Tak; Koh, Yong-Gon; Park, Kyoung-Mi; Choi, Chong-Hyuck; Jung, Min; Shin, Jucheol; Kim, Sung-Hwan
Abstract : Objectives: The aim of this study was to investigate the biomechanical effect of the anterolateral ligament (ALL), anterior cruciate ligament (ACL), or both ALL and ACL on kinematics under dynamic loading conditions using dynamic simulation subject-specific knee models. Methods: Five subject-specific musculoskeletal models were validated with computationally predicted muscle activation, electromyography data, and previous experimental data to analyze effects of the ALL and ACL on knee kinematics under gait and squat loading conditions. Results: Anterior translation (AT) significantly increased with deficiency of the ACL, ALL, or both structures under gait cycle loading. Internal rotation (IR) significantly increased with deficiency of both the ACL and ALL under gait and squat loading conditions. However, the deficiency of ALL was not significant in the increase of AT, but it was significant in the increase of IR under the squat loading condition. Conclusion: The results of this study confirm that the ALL is an important lateral knee structure for knee joint stability. The ALL is a secondary stabilizer relative to the ACL under simulated gait and squat loading conditions. Cite this article: Bone Joint Res 2019;8:509–517.